2012
DOI: 10.5493/wjem.v2.i4.78
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of longan flower and seed extracts for anti-cancer

Abstract: Polyphenol-rich plants are known to possess benefits to human health. Recent studies have revealed that many Traditional Chinese Medicines (TCMs) are rich sources of polyphenols and exhibit antioxidant and anti-inflammatory activities, and these TCMs have been shown experimentally to overcome some chronic diseases, including cancer. Longan flowers and seeds, two TCMs traditionally used for relieving pain and urinary diseases, have been revealed in our recent reports and other studies to possess rich amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 67 publications
1
20
0
3
Order By: Relevance
“…Total phenolics and the antioxidant capacities of ten flowers were measured in China; the results indicated that flowers were good sources of phenolics and antioxidants (Xiong et al, 2014). Other researchers have also indicated that flowers are rich in phenolic compounds and have great antioxidant activity, as well as the capacity to inhibit some chronic diseases (Besbes et al, 2013;Hsu, Fang, & Yen, 2013;Lin, Chung, & Hsu, 2012). In previous studies, large amounts of organic solvents were used to extract antioxidants from flowers (Xiong et al, 2014); however organic solvents are unsafe to researchers and unfriendly to the environment.…”
Section: Introductionmentioning
confidence: 97%
“…Total phenolics and the antioxidant capacities of ten flowers were measured in China; the results indicated that flowers were good sources of phenolics and antioxidants (Xiong et al, 2014). Other researchers have also indicated that flowers are rich in phenolic compounds and have great antioxidant activity, as well as the capacity to inhibit some chronic diseases (Besbes et al, 2013;Hsu, Fang, & Yen, 2013;Lin, Chung, & Hsu, 2012). In previous studies, large amounts of organic solvents were used to extract antioxidants from flowers (Xiong et al, 2014); however organic solvents are unsafe to researchers and unfriendly to the environment.…”
Section: Introductionmentioning
confidence: 97%
“…With increasing evidence that free radicals induce oxidative stress during the development of various diseases, the function of radical‐scavenging antioxidants has received much attention. Some selected flowers are rich in phenolic compounds and have great antioxidant activity, as well as the capacity to inhibit chronic disease (Lin and others ; Besbes Hlila and others ; Hsu and others ). Antioxidant capacity of some flowers measured from methods such as DPPH (Xu and others ), ABTS (Cai and others ) was estimated, however, the method used in evaluating the antioxidant capacity of edible flowers is often limited to a single method in vitro ; and various methods based on different principles should be applied to evaluate the antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Các hợp chất flavonoid và phenolic cũng hiện diện trong quả nhãn [3]. Do đó, quả nhãn có tác dụng chống oxy hóa và ngừa ung thư hiệu quả [4].…”
Section: đặT Vấ N đềunclassified